Hubungan Pengetahuan, Perilaku, dan Pengelolaan Jamban dengan Kejadian Diare di Wilayah Puskesmas Bogor Selatan 2022: Relationship between Knowledge, Behavior and Latrine Management with the Incidence of Diarrhea in the South Bogor Community Health Center Area 2022 - Sari, Dia Nur Rama; Fadillah, Randy; Pratiwi, Santi Tri; Purwitasari, Wulan; Amalia, Aura (MPI Press, 2023)
Background: Diarrhea is a disease with signs of changes in loose stools until they melt and an increase in the frequency of bowel movements 3 or more times a day. Based on the pattern of causes of death for all ages, diarrhea is the 13th leading cause of death with a proportion of 3.5%. Meanwhile, based on infectious diseases, diarrhea is the third leading cause of death after TB and pneumonia. The population in this study were residents of South Bogor City. Objectives: To find out the factors that influence the incidence of diarrhea in Bogor City to be used as an intervention and implementation step in an effort to reduce the incidence of Non-Communicable Diseases, especially diarrheal diseases in the South Bogor Health Center area. Method: The sample in this study was 33 respondents using the simple random sampling method. The data was collected using a questionnaire, then the data was processed and analyzed using the Microsoft Excel program. Data analysis included univariate analysis by looking for the frequency distribution. Result: The results of data collection showed that the percentage of several indicators, namely knowledge, latrine management and behavior, which were the trigger for the incidence of diarrhea was behavioral behavior with the results of good behavior as many as 18 (54.5%), and unfavorable behavior 15 (45.5)%. While knowledge, it was found that, for poor knowledge as many as 8 (24.2%) had good knowledge as many as 25 (75.8%) respondents. For latrine management, 10 (30.3%) had unhealthy latrine management and 23 (69.7%) respondents had healthy latrine management. Conclusion: The conclusion of this study, although respondents have a good level of knowledge, it is not necessarily the respondents have good diarrhea prevention behavior, because it is proven that even though respondents have good knowledge, they have poor diarrhea prevention behavior. For not applying it in behavior.